2009
DOI: 10.4028/www.scientific.net/kem.419-420.761
|View full text |Cite
|
Sign up to set email alerts
|

Using AHP and TOPSIS Approaches in Nuclear Power Plant Equipment Supplier Selection

Abstract: Comparing with others, the supply chain of nuclear power plant (NPP) has its special characteristics, which not only on product safety, but also on the life cycle of supplier as well as requirement of environment, the selection of the appropriate supplier requires independent evaluation index system. For these reasons, based on establishing an evaluation index system, an integrated framework is proposed to approach the supplier selection problem in NPP supply chain systems utilizing analytical hierarchy proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…The final decision is accomplished by a committee including five members with the predefined voting power V = (10,9,8,7,6), the result by WBF is shown in Fig. 11.…”
Section: Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The final decision is accomplished by a committee including five members with the predefined voting power V = (10,9,8,7,6), the result by WBF is shown in Fig. 11.…”
Section: Criteriamentioning
confidence: 99%
“…He highlighted that the key to accuracy in TOPSIS was to obtain an accurate weight. As methods merging AHP/ANP into TOP-SIS had been exploited and applied in a variety of fields [8][9][10][11], Yu and Bai [12] proposed a methodology based on interval-valued AHP and triangular fuzzy number to facilitate the evaluation process. Wang and Lee [13] developed a novel approach that involves end-users into the whole decision making process which could be used for software outsourcing problem.…”
Section: Related Workmentioning
confidence: 99%
“…Tables (2), 3, and (4) show the normalization matrix for the different methods. The weights of criteria are determined using pairwise comparison matrix as shown in table (5). We get information by asking the specialists in this field.…”
Section: Case Studymentioning
confidence: 99%
“…Yanpirat and V. Panjarongkha [4], used AHP as a ranking method for the group decision-making of site selection for water fabrication plant in Thailand.G. Yang, W. J. Huang, and L. L. Lei [5], used an integrated framework is proposed to approach the supplier selection problem in NPP supply chain systems utilizing AHP and improved TOPSIS.K. R. Gaurh, I. Khan, and M. Ghosh [6], utilized AHP and TOPSIS Method for solving the quandary of Material Handling Equipment cull in different shops of automobile industry.A.…”
mentioning
confidence: 99%
“…In previous studies, the methodologies utilizing BBN and AHP have been formulated for supporting decision-making processes. Limiting to nuclear field, the applications for the risk analysis [10][11][12][13], decision-making support [14,15], and the evaluation of systems' importance [16][17][18] were reported as examples of using BBN and AHP. Differently from the previous applications, this study suggested a method of how to model a BBN and to assign probability information to the BBN model using the results of AHP such that ultimately the model enables prioritizing accident precursors for nuclear accidents.…”
Section: Introductionmentioning
confidence: 99%